Pengamatan Teknik Pengoperasian Alat Tangkap Rawai Tuna (Tuna Long Line) di KM.Mutiara 26 Perairan Samudera Hindia - Katili, Lidya; Santoso, Heru; Putri, Elsari Tanjung; ramadhani, ahijrah; Tolawo, Rocky Geraldo (Jurusan Ilmu Kelautan dan Perikanan Politeknik Negeri Pontianak, 2024)
The tuna longline is a commonly used fishing gear among fishermen, especially in Benoa, Bali, for capturing large pelagic fish, primarily tuna, in offshore waters over an extended period. This study aims to identify the techniques for operating tuna longlines and to observe the handling process of the catch on the KM Mutiara 26 vessel. The research employs a qualitative descriptive analysis method. Findings indicate that the longline operation on KM Mutiara 26 involves preparatory steps followed by three operational phases: setting, soak time, and hauling. The fishing operations were conducted in the Indian Ocean at coordinates 30° – 32° South Latitude and 103° East Longitude. KM Mutiara 26 is a 122 GT fiberglass vessel powered by a 671 KW Cummins engine and equipped with 11 refrigerated holds. The vessel operates on a two-month cycle. The main catch species was southern bluefin tuna (Thunnus maccoyii), with a total of 242 fish, while the lowest catch was albacore (Thunnus alalunga), with 24 fish. Fish handling involved a four-step process, and storage of the catch was carried out using a freezing method.